Twin peaks: Convergence empirics of economic growth across Indian States - Sanghamitra Bandyopadhyay (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper documents the convergence of incomes across Indian states over the period 1965 to 1998. It departs from traditional analyses of convergence by tracking the evolution of the entire income distribution, instead of standard regression and time series analyses. The findings reveal twin-peaks dynamics – the existence of two income convergence clubs, one at 50 per cent, another at 125 per cent of the national average income. Income disparities seem to have declined over the sixties, only to increase over the following three decades. The observed polarisation is strongly explained by the disparate distribution of infrastructure and to an extent by a number of macroeconomic indicators; that of, capital expenditure and fiscal deficits.
Keywords: C23; E62; O53; 330; convergence clubs; conditional convergence; distribution dynamics; infrastructure; capital investment; macroeconomic stability; panel data; India; Entwicklungskonvergenz; Regionale Disparität; Teilstaat; Indien